2021
DOI: 10.3390/v13030383
|View full text |Cite
|
Sign up to set email alerts
|

Endogenization of a Prosimian Retrovirus during Lemur Evolution

Abstract: Studies of viruses that coevolved with lemurs provide an opportunity to understand the basal traits of primate viruses and provide an evolutionary context for host-virus interactions. Germline integration of endogenous retroviruses (ERVs) are fossil evidence of past infections. Hence, characterization of novel ERVs provides insight into the ancient precursors of extant viruses and the evolutionary history of their hosts. Here, we report the discovery of a novel endogenous retrovirus present in the genome of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Additionally, Grant et al developed a diagnostic method for distinguishing endogenous and exogenous SRV [ 65 ]. Zhu et al demonstrated that infection with SRV-8, a newly isolated SRV subtype, triggers autophagy and apoptotic pathways in Jurkat T lymphocytes [ 66 ]. Togami et al found that zidovudine and tenofovir disoproxil fumarate, in sub-micromolar to nanomolar dosages, potently inhibit SRV-4 infection; conversely, non-nucleoside reverse transcriptase inhibitors and protease inhibitors showed no activity against SRV-4 [ 67 ].…”
Section: Simian Retrovirusesmentioning
confidence: 99%
“…Additionally, Grant et al developed a diagnostic method for distinguishing endogenous and exogenous SRV [ 65 ]. Zhu et al demonstrated that infection with SRV-8, a newly isolated SRV subtype, triggers autophagy and apoptotic pathways in Jurkat T lymphocytes [ 66 ]. Togami et al found that zidovudine and tenofovir disoproxil fumarate, in sub-micromolar to nanomolar dosages, potently inhibit SRV-4 infection; conversely, non-nucleoside reverse transcriptase inhibitors and protease inhibitors showed no activity against SRV-4 [ 67 ].…”
Section: Simian Retrovirusesmentioning
confidence: 99%
“…In contrast to classes I and III, the class II ERVs have a more restricted host range, comprised mainly of mammals and birds; however, they have also recently been detected in amphibians [6][7][8]. Among class II ERVs, full-length endogenous betaretroviruses have been detected in the genomes of livestock [9][10][11][12], rodents [9,13], primates [9,14,15], bats [16,17], and the common brushtail possum (Trichosurus vulpecula) [18]. Betaretrovirus-related elements have been previously detected in wild cervid genomes such as caribou (Rangifer tarandus) and white-tailed deer (Odocoileus virginianus) utilising PCR assays targeting conserved regions of the retroviral pro and/or pol genes; however, these elements still remain uncharacterised [6].…”
Section: Introductionmentioning
confidence: 99%